P31 Assessing the effectiveness of tuberculosis (TB) screening in new entrant healthcare workers using different time cut-offs to define high risk individuals. (14th November 2013) - Morton, R; Bintley, K; Alexander, Z; Kahr, V
Abstract : Introduction and Objectives: NICE (2011) and the Department of Health (2007) provide guidance for occupational health departments for TB clearance in healthcare workers. Previous work from the London Consortium of Occupational Health Providers (LCOHPS) shows a marked variation in practice, notably in the criteria for defining high risk individuals. The length of time in the UK for an individual from a high TB endemic area (defined as an incidence of 40 per 100, 000 or greater) to be considered as low risk ranges from 6 months to >5 years. We performed a retrospective study of new trust employees to see if changing the definition of a high risk individual would impact on the effectiveness of our screening programme. Methods: We performed a retrospective study of 40 new employees at our trust between 2008 and 2012. Cases were selected on the basis of a positive QuantiFERON-TB Gold test at occupational health screening. Demographic data, including date of UK entry, were collected and analysed. Results: Results are summarised in Table 1 . Conclusions: Changing the definition of a high risk individual by reducing the cut-off time since entry to the UK may have both financial and time-saving consequences. However, our data show that a significant proportion of healthcare workers with latent TB infection, and in some cases active TB infection, would be missed by reducing the cut-off to 1 year. Screening of healthcare workers is an important aspect in the prevention and control of TB. Reducing the effectiveness of this screening exposes patients to increased risk. In view of these data, we would not recommend reducing the cut-off time for the definition of a high risk individual to less than 5 years.